Political participation of the differently abled in the association of disabled persons-Iloilo (ADP-1) - Basco, Ellinore Josephine C.
The study is done in order to determine how the differently abled in the Association of disabled persons in Iloilo (ADP-l) participate in political activities and to examine the factors that influences the extent of their political involvement.